2016
DOI: 10.1161/circheartfailure.116.003259
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Patients With Myocarditis Listed for Heart Transplantation

Abstract: Background-Myocarditis can cause dilated cardiomyopathy resulting in end-stage heart failure requiring advanced therapies. There is little contemporary information on the clinical progression, need for mechanical circulatory support, and outcomes of orthotopic heart transplantation of these patients. Despite higher allosensitization, patients with myocarditis had similar post-transplant rejection, retransplantation, and survival rates compared with other groups. Conclusions-Patients with the diagnosis of myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
3
14
1
Order By: Relevance
“…Long-term implantable left ventricle assist devices (LVADs) are rarely used to provide adequate circulation for a more extended time period to allow the resolution of myocarditis and bridge a patient from emergent temporary MCS to HTx, which is the final option for treating critically ill patients affected by myocarditis. HTx survival is comparable to that of patients with other types of HF as shown in a recent series, although higher rates of relapses have been demonstrated, especially in patients with GCM undergoing HTx ( 36 , 37 ). Once patients with FM recover from cardiogenic shock, pharmacological treatment for HF, including beta-blockers, diuretics, angiotensin-converting enzyme inhibitors or angiotensin-II receptor blockers, should be initiated according to current consensus ( 38 ).…”
Section: Introductionsupporting
confidence: 55%
“…Long-term implantable left ventricle assist devices (LVADs) are rarely used to provide adequate circulation for a more extended time period to allow the resolution of myocarditis and bridge a patient from emergent temporary MCS to HTx, which is the final option for treating critically ill patients affected by myocarditis. HTx survival is comparable to that of patients with other types of HF as shown in a recent series, although higher rates of relapses have been demonstrated, especially in patients with GCM undergoing HTx ( 36 , 37 ). Once patients with FM recover from cardiogenic shock, pharmacological treatment for HF, including beta-blockers, diuretics, angiotensin-converting enzyme inhibitors or angiotensin-II receptor blockers, should be initiated according to current consensus ( 38 ).…”
Section: Introductionsupporting
confidence: 55%
“…The proportion of female COVID‐19 patients with myocarditis was similar to that reported by Ammirati et al (34.1% vs. 38.9%) 13 and comparable to myocarditis caused by other pathogens than SARS‐CoV‐2 15,36–38 …”
Section: Discussionsupporting
confidence: 87%
“…The proportion of female COVID-19 patients with myocarditis was similar to that reported by Ammirati et al (34.1% vs. 38.9%) 13 and comparable to myocarditis caused by other pathogens than SARS-CoV-2. 15,[36][37][38] Our study demonstrated that the highest absolute numbers of myocarditis cases were seen during spring (March/April) and in winter (November/December), along with the highest numbers of hospitalized COVID-19 patients 5,18 and thus, following the seasonal variations of viral infections. 18,27 In this context, the highest relative numbers of myocarditis, in turn, were identified in the summer, suggesting that in summer was the risk of developing myocarditis at its maximum.…”
Section: Resultsmentioning
confidence: 57%
“…The severity and prognosis of myocarditis varies greatly, from asymptomatic episodes with spontaneous improvement to severe heart failure or other cardiac complications. In the acute phase systolic dysfunction, ventricular arrhythmias and sudden deaths may ensue and in the chronic phase it can result in heart failure, which may require advanced treatment such as left ventricular assist devices and transplantation in severe cases [10].…”
Section: Discussionmentioning
confidence: 99%